Pengaruh Word of mouth, Iklan dan Atribut Produk Terhadap Keputusan Pembelian dan Loyalitas Konsumen - haryanto, jony oktavian; Yunita, A (Jurnal Manajemen Teknologi, 2012)
At the end of November 2010, Magnum ice cream suddenly became a hot topic in many mass media and among youths. This product was difficult to be found in the market and became a real craze for ice cream lovers in Indonesia. The selling of Magnum ice cream increased 20 times in 4 months. Based on these phenomena, this research aims at identifying factors that influence consumers’ decision in purchasing the product and their responses after their purchase. The data was analyzed using structural equation modeling with the software Lisrel 8.8. The result shows that advertisement and product attributes had a significant impact on purchase decision, whereas word of mouth did not have any significant impact. Furthermore, purchase decision that had been made by the consumer had a significant impact on their behaviors after purchasing. Those behaviors are the consumers’ loyalty and the word of mouth.